PENERAPAN KONSELING BEHAVIORISTIK DENGAN TEKNIK SELF MANAGEMENT UNTUK MENGATASI PERILAKU MEMBOLOS SAAT PEMBELAJARAN DARING - Niken Vera Wesmi; Arista Kiswantoro; Santoso Santoso (Jurnal Muria Research Guidance and Counseling (MRGC), 2022)
The purpose of this study: 1. To describe the factors that cause student truancy behavior during online learning. 2. Overcoming truancy behavior during online learning through behavioristic counseling with self-management techniques. The subjects of this study were 2 students of SMA PGRI 2 Kayen who had truant behavior during online learning.  Based on the results of the study, it can be concluded that caused by internal factors and external factors. The factors that cause AK and DC to have truant behavior are caused by the lack of parental attention, as well as a sense of laziness from within. After counseling using a behavioristic approach and self-management techniques, AK and DC were able to gradually eliminate maladaptive behavior and were able to manage themselves not to do bad deeds. Based on these results, the behavioristic counseling approach with self-management techniques is able to overcome truancy behavior during online learning.